Rapid Determination of Carboplatin and Docetaxel Using RP-HPLC with PDA Detector - Devi, Potturi Rama; Rambabu, Kantipudi (Novel Aspects on Pharmaceutical Research Vol. 7, 2023)
Objective: In the current investigation, to separated and validate the cancer healing drugs (Carboplatin and Docetaxel) through the HPLC (e-2695) instrument containing a PDA detector. Methods: A simple, selective, validated and well-defined stability that shows isocratic RP-HPLC methodology for the quantitative determination of Carboplatin and Docetaxel. The chromatographic strategy utilized Symmetry C18 column of dimensions 150x4.6 mm, 3.5 micron, using isocratic elution with a mobile phase of acetonitrile and 0.1% ortho phosphoric acid (40:60). A flow rate of 1 ml/min and a detector wavelength of 225 nm utilizing the PDA detector were given in the instrumental settings. Recovery, specificity, linearity, accuracy, robustness, ruggedness were determined as a part of method validation and the results were found to be within the acceptable range. Validation of the proposed method was carried out according to an international conference on harmonization (ICH) guidelines. Results: LOD and LOQ for the two active ingredients were established with respect to test concentration. The calibration charts plotted were linear with a regression coefficient of R2>0.999. Conclusion: The proposed method to be fast, simple, feasible and affordable in assay condition. During stability tests, it can be used for routine analysis of production samples and to verify the quality of drug samples during stability studies.